Improved biological performance of magnesium by micro-arc oxidation - Ma,W.H. (2015)
Magnesium and its alloys have recently been used in the development of lightweight, biodegradable implant materials. However, the corrosion properties of magnesium limit its clinical application. The purpose of this study was to comprehensively evaluate the degradation behavior and biomechanical properties of magnesium materials treated with micro-arc oxidation (MAO), which is a new promising surface treatment for developing corrosion resistance in magnesium, and to provide a theoretical basis for its further optimization and clinical application. The degradation behavior of MAO-treated magnesium was studied systematically by immersion and electrochemical tests, and its biomechanical performance when exposed to simulated body fluids was evaluated by tensile tests. In addition, the cell toxicity of MAO-treated magnesium samples during the corrosion process was evaluated, and its biocompatibility was investigated under in vivo conditions. The results of this study showed that the oxide coating layers could elevate the corrosion potential of magnesium and reduce its degradation rate. In addition, the MAO-coated sample showed no cytotoxicity and more new bone was formed around it during in vivo degradation. MAO treatment could effectively enhance the corrosion resistance of the magnesium specimen and help to keep its original mechanical properties. The MAO-coated magnesium material had good cytocompatibility and biocompatibility. This technique has an advantage for developing novel implant materials and may potentially be used for future clinical applications.